Unraveling the Influence of Lifestyle Choices on Microbiota Diversity - A Comprehensive Review - Tomasz Seredyński; Wojciech Mądry; Aleksandra Mazurkiewicz; Magdalena Kołodziej; Joanna Męczyńska; Nazarii Saiuk; Michał Andrzej Kozicz; Adriana Wojciechowska; Justyna Marcicka; Weronika Salasa (Kazimierz Wielki University, 2024)
In recent years, there has been a growing interest in the interplay between lifestyle choices, particularly non-pharmacological methods, and their profound impact on gut health. This burgeoning interest is fuelled by a growing body of research highlighting the pivotal role of the gut microbiota in maintaining overall health and well-being. Aim of the study: The aim of this review is to explore the nexus between an optimal health-related choices and gut microbiota composition, highlighting the latest research findings and insights into how dietary patterns, physical activity, psychological stress and sleep quality influence microbial diversity and functionality. Materials and methods: A comprehensive examination of scientific literature available in the PubMed and Google Scholar databases was undertaken. The search strategy incorporated keywords such as "gut", "gut microbiota", "exercise", "diet", "stress" and "circadian rhythm" to identify relevant articles. Results: The literature review findings unequivocally reveal an increased diversity in the gut microbial community and a favourable balance between commensal and pathogenic bacteria, as well as overall gut health, including integrity and functionality, attributable to adherence to a healthy lifestyle. These findings highlight the intricate interplay between lifestyle factors and colon microbial composition. Conclusions: Although initial findings are encouraging, additional investigation into the potential impact of gut microbiota on health, particularly in the long term, is indispensable. Moreover, the limitations inherent in current research methodologies, such as small sample sizes, variability in study designs, and inconsistencies in findings, underscore the need for robust, well-controlled studies to validate and expand upon existing findings. Robust studies are necessary to develop targeted interventions for optimizing gut health.